Arsitektur Biofilik Sebagai Strategi Desain Terapeutik : Konseptualisasi Rumah Sakit Jiwa di Kota Palu - Timbang, Gator; Sirajuddin, Zaenal; Luthfiah, Luthfiah; Syahrullah, M. Rachmat (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2025)
This study aims to explore and formulate therapeutic design strategies based on biophilic architecture in the design of mental hospitals in Palu City. The research begins with the identification of biophilic architectural elements that possess therapeutic value within the context of mental healthcare facilities, followed by an analysis of the psychological and spatial needs of patients and users of mental hospitals in Palu, using a biophilic approach. The study adopts a qualitative-descriptive approach grounded in both conceptual and contextual foundations. The main focus is to formulate a mental hospital design concept based on the principles of biophilic architecture as a therapeutic strategy aligned with the social, cultural, and ecological characteristics of Palu City. The process involves conceptual design methods, site context analysis, and user needs assessment, which lead to the synthesis and formulation of a comprehensive design concept. Findings from this study indicate that biophilic architecture holds significant potential as a therapeutic design strategy in the development of mental healthcare facilities, especially in post-disaster areas such as Palu City. This approach not only offers more humane spatial solutions that support psychological recovery, but also addresses ecological, social, and disaster resilience challenges faced by the Palu community